From gender gaps to gender-transformative climate-smart agriculture - Huyer, Sophia; Loboguerrero Rodriguez, Ana María; Chanana, Nitya; Spellman, Olga (Elsevier, 2024)
To date, much of the research on the nexus between gender and climate has emphasized the negative impacts on women, in terms of their increased vulnerability to climate-related shocks. Women in developing countries rely predominantly on natural resources for their farming activities, household needs, and caregiving roles. For many women in these contexts, access to important resources such as credit, information, extension and agricultural services, as well as training in technology, is largely limited due to social norms and stakeholder biases. This affects their agency at home and within their communities 1••, 2•, 3••, 4.